Arthroscopic posterior-inferior capsular release in the treatment of overhead athlete with GHIRD: a case report - Adnyana Christian, Stedy; Aryana, I. G. N. Wien; Wirakarna, I. B. Aditya; Angganugraha P. J., I. G. B. Indra; Trysna Andika, Komang Arie; Ambong, Hafidz Addatuang; Pranata, Soehartono Hadi (International Journal of Research in Medical Sciences, 2018)
Glenohumeral internal rotation deficit (GHIRD) is one of most controversial joint diseases in terms of diagnosis and treatment. The use of arthroscopy has improved the recognition of pathologic findings in glenohumeral internal rotation deficit (GHIRD) and allowed a better understanding of the etiology of it and the correlation between symptoms and lesion patterns. We present our technique for arthroscopic posterior-inferior capsular release in athlete with symptomatic glenohumeral internal rotation deficit (GIRD) that was unresponsive to nonoperative treatment and was preventing him from returning to sport. By this technique resulted in a successful outcome. We evaluate a 28 years old male with right shoulder pain and limitation in abduction internanal rotation after 3 months conservative treatment. We performed Arthrospcopic posterior-inferior capsular release. After 2 months correspondingly, we performed follow-up assessments on shoulder function (using the ases and rowe score) and pain (using a visual analogue scale) were made. Arthroscopic posterior-inferior capsular release can be recommended as a reasonable operative solution for overhead athletes with symptomatic GIRD that has not responden to conservative management. Evaluation of patient in whom we performed arthroscopic repair base on ases and rowe score. Arthroscopic posterior-inferior capsular release showed satisfactory shoulder function after 2 months follow up correspondingly.